SERAPAN BAHASA ARAB DAN SEMANTIK DALAM SYAIR BISMILLAHIRRAHMANIRRAHIMI KARYA HAMZAH FANSURI - Emi Suhemi (An-Nahdah Al-'Arabiyah, 2023)
This study aims to find out how far Arabic influences Hamzah Fansuri's thoughts in his poetry. This research uses the approach of psychology (morphology) and semiotics. The research method used is descriptive analysis research by conducting library research and content analysis. As for the data collected, it can be concluded that Hamza Fansuri's thoughts in describing God, especially in the Bismillahirrahmanirrahimi poem, there are more than 30 (thirty) Arabic absorptions and there is semiotics from these Arabic words.